Applying UNESCO’s ICT Framework to Enhance Technology Literacy Skills of Teachers - Muhammad Daud Ghumman (IJLTP, 2025)
In the moment's technology-driven world, teachers need to be technologically knowledgeable. This includes having the knowledge and skills to effectively use different technology tools and applications. This study was conducted to assess the impact of a professional development program on technology literacy skills developed through teachers’ training program developed on ICT competencies by using UNESCO’s ICT framework. The study's population comprised all secondary school teachers at Govt. Central Model School, Lower Mall, Lahore. The total population consisted of 68 teachers. To ensure a balanced representation of both genders, a proportionate stratified random sampling technique was employed. This method involved dividing the population into two strategy male and female and selecting an equal proportion of participants from each group. The final sample comprised 34 teachers, representing 50% of the total population. To commence the study pre-test post-test design was used. The experiment was conducted while applying training on ICT competencies to enhance teachers' ICT capabilities. The study concentrated on ICT literacy areas i.e. computer operations, software operations, and digital communication. Results showed a positive change in the teachers' ICT faculty situations after the training program. A significant positive increase in post-test competencies related to the use of the Internet, World Wide Web (WWW), and email after the training program was also noted. This study recommends that regular professional development programs be organized for teachers to continuously enhance their ICT chops. Ongoing development can help teachers stay streamlined and complete in using technology.